The Basis of the Hadith on Capital as a Pillar of Education and Economic Welfare - Mohammad Fattah; Lailatul Mukarramah (Values: Jurnal Kajian Islam Multidisiplin, 2026)
Hadith is a primary source of Islamic law and plays an important role in regulating the life of the Muslim community, including in the economic sphere. Hadith not only explains the contents of the Qur’an but also serves as a practical guide for managing capital responsibly. This study employs a qualitative approach based on library research, allowing the researcher to examine primary and secondary literature in depth, including the Qur’an, Hadith collections (Shahih al-Bukhari, Shahih Muslim, at-Tirmidhi), as well as books and scholarly articles discussing Islamic economics, education, and economic ethics. The findings indicate that Hadith consistently emphasizes fundamental principles such as justice, honesty, the prohibition of riba, and the practice of ethical and transparent trade. These principles serve as a guide for Muslims in utilizing capital not merely for personal material gain but also for the collective welfare of society.